Keadilan (Sosial) dalam Perspektif Teologi Biblika - Kristanto, Billy (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
The struggle to bring about social justice is sometimes suspected of being a form of cultural Marxism. Is this view representative from a Christian theological perspective? Of course, the answer given will depend on our understanding of social justice itself. Thus, we need to look at several passages of Scripture to get a more balanced picture of this.